Genetic modifications designed for xenotransplantation attenuate sialoadhesin‐dependent binding of human erythrocytes to porcine macrophages. (20th September 2022) - Petitpas, Kaitlyn; Habibabady, Zahra; Ritchie, Veronica; Connolly, Margaret R.; Burdorf, Lars; Qin, Wenning; Kan, Yinan; Layer, Jacob V.; Crabtree, Juliet N.; Youd, Michele E.; Westlin, William F.; Magnani, Diogo M.; et al.
Abstract: The phenomenon of diminishing hematocrit after in vivo liver and lung xenotransplantation and during ex vivo liver xenoperfusion has largely been attributed to action by resident liver porcine macrophages, which bind and destroy human erythrocytes. Porcine sialoadhesin (siglec‐1) was implicated previously in this interaction. This study examines the effect of porcine genetic modifications, including knockout of the CMAH gene responsible for expression of Neu5Gc sialic acid, on the adhesion of human red blood cells (RBCs) to porcine macrophages. Wild‐type (WT) porcine macrophages and macrophages from several strains of genetically engineered pigs, including CMAH gene knockout and several human transgenes (TKO+hTg), were incubated with human RBCs and "rosettes" (≥3 erythrocytes bound to one macrophage) were quantified by microscopy. Our results show that TKO+hTg genetic modifications significantly reduced rosette formation. The monoclonal antibody 1F1, which blocks porcine sialoadhesin, significantly reduced rosette formation by WT and TKO+hTg macrophages compared with an isotype control antibody. Further, desialation of human RBCs with neuraminidase before addition to WT or TKO+hTg macrophages resulted in near‐complete abrogation of rosette formation, to a level not significantly different from porcine RBC rosette formation on porcine macrophages. These observations are consistent with rosette formation being mediated by binding of sialic acid on human RBCs to sialoadhesin on porcine macrophages. In conclusion, the data predict that TKO+hTg genetic modifications, coupled with targeting of porcine sialoadhesin by the 1F1 mAb, will attenuate erythrocyte sequestration and anemia during ex vivo xenoperfusion and following in vivo liver, lung, and potentially other organ xenotransplantation.